African ST173 Cryptococcus deuterogattii strains are commonly less susceptible to fluconazole: An unclear mechanism of resistance. (June 2020) - Bertout, S.; Roger, F.; Drakulovski, P.; Martin, A.S.; Gouveia, T.; Kassi, F.; Menan, H.; Krasteva, D.; Delaporte, E.; Bellet, V.
Highlights: All Ivorian Cryptococcus deuterogattii isolates were identified as ST173 by MLST. 64.3% (18/28) of isolates had a fluconazole (FCZ) MIC of ≥16 μg/mL. FCZ exposure increased AFR1 mRNA expression, especially in isolates with high FCZ MICs. Resistance mechanisms described in Cryptococcus neoformans were not involved in C. deuterogattii ST173 isolates. Abstract: Objectives: Fluconazole (FCZ), either alone or in combination, is often administered for treatment of cryptococcal meningitis, especially in sub-Saharan Africa. Its extensive use has led to the emergence of FCZ-resistant strains. The mechanisms underlying FCZ resistance are poorly documented for yeasts belonging to the Cryptococcus gattii species complex. The literature suggests that resistance could be due to mutations in and/or overexpression of the ERG11 gene (encoding the 14-α-demethylase) and efflux pumps such as MDR and AFR (two subclasses of ABC transporters). Here we highlight the presence of genotype VGII strains ( Cryptococcus deuterogattii ) from the Ivory Coast with a rare sequence type (ST173) associated with high FCZ minimum inhibitory concentrations (MICs) compared with strains originating from the Pacific Northwest (USA). Methods: Mechanisms of FCZ resistance were investigated in 28 Ivorian clinical C. deuterogattii isolates recovered from three patients during their antifungal treatment and follow-up. Results: The results demonstrated that: (i) these strains exhibited no mutations in the ERG11 gene; (ii) some strains had increased ERG11 and MDR1 mRNA expression, whilst AFR1 and AFR2 were not overexpressed in strains with high FCZ MICs compared with the expression levels for strains with low FCZ MICs; and (iii) exposure to FCZ in strains with high MICs induced AFR1 mRNA overexpression. Conclusion: This study demonstrated that the FCZ resistance mechanism commonly described in Cryptococcus neoformans was not responsible for resistance to FCZ in rare subtype strains.